The New Technological Revolution and the Third World (Revista Gestão & Conexões, 2013)
DOI: http://dx.doi.org/10.13071/regec.2317-5087.2013.2.2.6184.151-180The paper analyses the general characteristics of the new wave of technological innovations and explores its possible impact on Third World countries. The conceptual background used is the Kondratiev-Schumpeter theory of the long cycles of the economy.